Granulometric Characterisation and Distribution of Contemporary Fluvial Sediment in the Magoye River Sink, Southern Zambia - Muchanga, Manoah; Daniel, Mafwabo (European Journal of Applied Sciences, 2025)
The study granulometrically characterised the contemporary fluvial sediment deposited at selected cross-sections of the river using field sampling, GPS, GIS and laboratory analysis of sediment using sieves. The study calibrated what in our view, was the first-ever regression model (Phi-mm) with contextual relevance to Zambian river catchments and channels as opposed to those devised outside the African context. This model can potentially be extrapolated to immediate neighbouring catchments within the region that have similar hydrogeomorphological characteristics as the target river catchment in the study. On average, the downstream of the Magoye River bed was characterised by sediment of diverse particle sizes with those above 2 mm constituting 29% of sediment, especially near the bridge. The sediments of 1 mm diameter were also in the same magnitude. On average, the rarest occurring sediment type were those equal to or less than 0.1mm as these take long to settle due to their minute sizes. A large proportion of sediment with particle size between 2mm and >2mm settled within the first 7-8 Km from the Magoye Bridge, which also attracted high occurrence of river bed sand and stone quarrying and hence, the observed buffer zone and bed degradation. Sediment particles between 1mm and 0.5mm showed a high variable geospatial occurrence, but the latter drastically increased towards the mouth, which confirms the influence of particle size on settling time. Furthermore, sediment with grain size of 0.25mm showed a high variability across the channel bed as compared to those whose grain sizes were 0.1mm to 0.05mm, which were usually in stable equilibrium throughout the channel profile in terms of relative abundance. Their low percentage of occurrence signify their low density and high affinity to remain suspended for longer time. For instance, the only highest occurrence for sediment with grain size of 0.1mm was record around 26 km away from the bridge near the mouth where river flow power tend to be exceedingly low. This pattern, seem to suggest that, most sediment particles below 0.1mm ended up into the Kafue River as they never significantly settled on the Magoye River bed. This signals water quality issues in the receiving Kafue Flats and River. In conclusion, the granulometric study of contemporary fluvial sediment in the Magoye River provides valuable insights into the sediment dynamics and the potential implications for neighbouring river catchments in Zambia and the sub-region. The development of a regression model calibrated specifically for Zambian river catchments represents a significant advancement in the understanding of sediment transport and deposition in the region. The findings reveal a complex distribution of sediment particle sizes, with implications for sediment settling times and river bed characteristics. The downstream areas near the bridge exhibit diverse sediment sizes, with larger particles dominating, highlighting the impact of proximity to the bridge on sediment characteristics. Furthermore, the study underscores the influence of particle size on sediment settling patterns, with implications for sediment transport and water quality in the Kafue River. These findings have important implications for river management and conservation efforts in Zambia and neighbouring regions, providing a valuable foundation for further research and environmental protection initiatives within the catchments.